Profitability of momentum strategies during crisis: evidence from Finland during Covid-19 pandemic - Anttila, Julianna (My University, 2024)
Extensive research exists to support the profitability of momentum strategies, which rely on the continuation of past price trends. However, the source of the momentum anomaly remains largely unknown. Studies have found that momentum strategies experience significant negative returns during market recovery post periods of high market volatility and uncertainty, referred to as momentum crashes. This thesis exam-ines the impact of COVID-19 on the profitability of momentum strategies in the Finn-ish stock market. The methodology employs an event study as well as Single Index Models to test whether the returns of momentum portfolios are significantly affected by the COVID-19 crisis. The findings of this study indicate that cross-sectional momentum strategies were significantly negatively impacted by COVID-19. Deviating from the findings of some existing research, the momentum portfolios did not yield significant negative returns, but performed worse in comparison to the market than before the crisis in or became market neutral. The portfolios with different combinations of observation and holding periods were affected differently, where the portfolios with longer holding periods were typically impacted more in comparison to portfolios with short holding periods. Overall, this study suggests that the existing momentum crash research also applies to the Finnish stock market.
Keywords: COVID-19; pandemics; pricing; profitability; investments (economics); portfolios; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance